Suitability Analysis for Grouper Floating Net Cages - Adrian Hamzah; Juliana Juliana; Mulis Mulis (The NIKe Journal, 2018)
This study aims to analyze the physical and chemical quality of the waters and analyze the suitability of floating net cage (KJA) for grouper (Ephinepelus sp) aquaculture in the waters of Olele Village. The research method used is a survey method that is observing and determining the land of observation station points and the suitability matrix approach by measuring physical and chemical parameters. The results showed that Olele Village had the potential for the development of floating net cages (KJA) for grouper aquaculture and had two categories of suitability classes that were very suitable (S1) located at Station 1 and the appropriate category (S2) at Station 2 and Station 3. Keywords: Suitability; grouper; Ephinepelus sp; aquaculture; floating net cage; KJA